Decreased Immune Response in Alexithymic Women: A One-Year Longitudinal Study - Guilbaud, Olivier; Perrin, Claire; Curt, Florence; Chaouat, Gérard; Dugré-Le Bigre, Corinne; Strebler, Martine; Touitou, Catherine; Corcos, Maurice (Frontiers in Psychiatry, 2021)
Although previous cross-sectional studies suggested significantly decreased immune response in alexithymia, there is a lack of longitudinal studies. We sought to determine the reliability of the reported relationship between alexithymia and decreased immune response in a longitudinal study. Thirty-eight healthy women who had participated in a cross-sectional study were recontacted one year later. Of this sample, twenty-six were finally included: 13 females who had been found to be alexithymic, and 13 females who were classified as non-alexithymic under the 20-item Toronto Alexithymia Scale during the first phase of the study. A year later, they were still healthy women without any psychiatric disorders, their ages now ranging from 19 to 28 years old. Lymphocyte subset counts (CD4, CD8), in vitro production of interleukin 1 (IL-1β), IL-2, IL-4 and IL-10 by phytohemagglutinin stimulated peripheral blood lymphocytes, as well as serum cortisol levels, were compared between women with and without alexithymia. One year later, alexithymic women still had significantly lowered in vitro production of IL-2 and IL-4, with lowered IL-2/IL-10 ratio and a reduced percentage of CD4. This is the first ever published study assessing cytokine production during a follow-up. Although our results should be interpreted with caution due the small sample size, they suggest a sustained reduction in both major type 1 and type 2 cytokines while the former seems to be more affected. The potential long-term health impact, if any, is still to be determined.